Development of Google Sites-Based Parenting Management Model to Improve the Role of Parents in Shaping A Child’s Character and Development - Septhy Saputri Lamba; Yari Dwikurnaningsih; Sophia Tri Satyawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to develop a Google Sites-based parenting management model to support the role of parents in shaping a child's character and development. This method used research and development with the Borg & Gall model, which involved research, planning, initial product development, field testing, and leading product revisions. The study took place at TK Kristen 03 Eben Heazer, Salatiga, involving school principals, teachers, and parents. Data collection techniques included interviews, documentary studies, observations, and questionnaires. Data analysis utilized qualitative and quantitative descriptive methods. The development of the "Family-Link" parenting management model received validation scores of 83% from IT experts and 88% from Management experts. The trial results from school principals, teachers, and parents sequentially showed 84.61%, 91.78%, and 87.30%. Therefore, "Family-Link" falls into the category of being ready for effective use as a parenting management tool. The "Family-Link" website provides school information, documentation of children's activities, a communication forum for parents and teachers, parenting resources, a calendar, and forms for evaluation and sharing parental experiences. In conclusion, the research findings demonstrate that the "Family-Link" parenting management model effectively supports the administration of parenting programs in schools and enhances parental involvement in child development.